Determinants of psychological well-being among single young adults in Malaysia: Attitudes towards singlehood, stereotypes and social support - Kan, Vivian; Ngo, Da Long; Wong, Jia Man (2023)
This study investigated the relationship between singlehood, negative stereotypes towards single individuals, social support, and psychological well-being among young adults in Malaysia. Despite initial hypotheses, the results indicated non-significant correlations between attitudes towards singlehood and psychological well-being, negative stereotypes and psychological well-being, and social support and psychological well-being. Cultural variations, societal expectations, and individual experiences in Asian societies, where marriage is culturally significant, may contribute to the lack of significance observed in these relationships. While past studies have suggested negative stereotypes about singlehood, this study demonstrates that such stereotypes may not significantly impact psychological well-being. Additionally, social support, while moderately correlated, did not significantly predict psychological well-being. Theoretical implications highlight the role of Maslow's Hierarchy and social support theories, while practical implications suggest the need for awareness campaigns, educational programs, and policy changes to create a supportive environment for single young adults. Limitations of self-reported measures and cross-sectional design are acknowledged, suggesting the use of objective measures and longitudinal studies for future research. Despite the results not aligning with the hypotheses, this study contributes to understanding singlehood, stereotypes, social support, and psychological well-being in the context of Malaysian young adults and offers directions for future research.